2023
DOI: 10.1002/nafm.10894
|View full text |Cite
|
Sign up to set email alerts
|

Salvage using electrofishing methods caused minimal mortality of burrowed and emerged larval lampreys in dewatered habitats

Abstract: ObjectiveHuman‐induced dewatering of freshwater habitats causes mortality of larval lampreys (family Petromyzontidae). Salvage by electrofishing at dewatering events is assumed to reduce this mortality, but to our knowledge this assumption remains unassessed.MethodsWe estimated mortality of salvaged larval lampreys (Lampetra spp. and Pacific Lamprey Entosphenus tridentatus) within 24 h following collection at field dewatering events in July and October. To assess when salvage may reduce mortality, we compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(33 citation statements)
references
References 36 publications
1
32
0
Order By: Relevance
“…Like laboratory findings, a field evaluation of salvage techniques reported that the mortality risk for larval lampreys declined significantly with increased size (Harris et al. 2023). Taken together, these findings highlight the vulnerability of small lampreys to dewatering.…”
Section: State Of the Sciencementioning
confidence: 95%
See 4 more Smart Citations
“…Like laboratory findings, a field evaluation of salvage techniques reported that the mortality risk for larval lampreys declined significantly with increased size (Harris et al. 2023). Taken together, these findings highlight the vulnerability of small lampreys to dewatering.…”
Section: State Of the Sciencementioning
confidence: 95%
“…2021; Harris et al. 2023). Laboratory and field research suggests that survival associated with a dewatering event varies based on larval size, whether the larvae exhibit emergence, the duration of exposure, and environmental conditions (Liedtke et al.…”
Section: State Of the Sciencementioning
confidence: 99%
See 3 more Smart Citations